2017
DOI: 10.1016/j.pec.2017.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Patient-centered communication in digital medical encounters

Abstract: Objective Patients are increasingly using the secure messaging function available through online patient portals to communicate with their health care providers, yet little is known about the characteristics of conversations that occur. The goal of this study is to describe the types of messages initiated by patients communicating via patient portals and to assess whether providers employ patient-centered strategies in their electronic responses. Design A total of 193 messages from 58 message threads between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…Experiences related to health care professionals’ work were divided into 5 subthemes, which related to the increased workload [ 39 , 41 , 42 , 44 - 48 , 50 ], more efficient work [ 42 , 44 , 47 , 48 , 50 , 51 ], experiences of fear and discomfort [ 41 , 43 , 46 , 49 , 50 ], increased awareness of patients’ situations [ 41 , 43 , 48 ], and lack of time and expertise required for portal communication [ 42 , 43 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Experiences related to health care professionals’ work were divided into 5 subthemes, which related to the increased workload [ 39 , 41 , 42 , 44 - 48 , 50 ], more efficient work [ 42 , 44 , 47 , 48 , 50 , 51 ], experiences of fear and discomfort [ 41 , 43 , 46 , 49 , 50 ], increased awareness of patients’ situations [ 41 , 43 , 48 ], and lack of time and expertise required for portal communication [ 42 , 43 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Online interaction between patients and providers has previously been shown to be problematic, with a discrepancy between the concerns being voiced by patients and the nature of replies being provided by HCPs, particularly in regard to the use of inclusive and supportive language [ 39 ]. Interviews with HCPs indicated that there were concerns about finding the right tone in potential online communication with people with diabetes, especially in the absence of social cues that they would use to tailor their communication and advice in face-to-face encounters.…”
Section: Discussionmentioning
confidence: 99%
“…Our knowledge of best practices for PCC in the electronic age is emerging. Yet, we do know that when patients are able to conduct a dialogue with providers using secure messaging, few providers responded using PCC practices [65]. However, advocates of OpenNotes report that patient's access to notes facilitates their ability to share information with care partners, correct mistakes, and partner with providers [66].…”
Section: Discussionmentioning
confidence: 99%